Fostering problem solving and performance assessment among Malaysian mathematics teachers - Khalid, Madihah (Penerbit UTM Press, 2017)
Problem solving is considered important in the learning of mathematics because it develops the logical thinking aspect of doing mathematics. Thus it allows students to reason, communicate ideas, and employ knowledge to new and different variation of problems and situations. In the most recent Programme for International Student Assessment (PISA) result on problem-solving, Malaysian 15 year olds scored 422, which is significantly below the OECD average of 500. One of the causes for the unsatisfactory performance is that our students’ ability to solve problems are not nurtured at the mainstream school. This paper will touch on some implication from the PISA result, the pedagogical approach of Malaysian mathematics teachers in teaching and learning of mathematics, and suggestions on how to implement lesson study to encourage teaching of mathematics through problem solving. At the same time, effective assessment of problem solving requires more than just looking at answers, it also involves a thorough analysis of the process. Therefore, in the evaluation process of problem solving in mathematics, the role of performance assessment will be examined – for example how it can be implemented together to satisfy the School-based assessment needs. Finally, results of a few research on problem solving and lesson study approach will be presented. The author’s own research on lesson study, problem solving and performance assessment will be used as examples and discussed.